Plasmonic 2D nanopillar arrays in high index and gradient index medium for subtractive optical filtering - Bingi, Jayachandra (2016)
2D metal nanopillar arrays in media of constant and gradient refractive indices are simulated and their subtractive colour filtering features are demonstrated. These results are expected to contribute to the next generation display technologies.